Test item construction and its appropriateness towards indicators - Jumainah Jumainah; Muliyadi Muliyadi; Norliani Norliani (Lentera: Jurnal Ilmiah Kependidikan, 2017)
Students of Faculty of Teacher Training usually will undergo field experience practice when they are at higher semester, usually at 6th and 7th semester. In their sixth semester they will undergo field experience practice I (PPL I), and at seventh semester, they will undergo field experience practice II (PPL II). In PPL II, they will undergo pre-service teacher training in the form of classroom teaching involvement. They will be given an opportunity to conduct a teaching practice at school where they are assigned. It is worth knowing that although all the students who undergo PPL have been provided with some theoretical knowledges related to teaching and learning process, such as how to teach in class, how to conduct an evaluation, how to construct testitem, etc, yet, they still have experience some problems in the field. One of the most outstanding problems the writers found and has drawn the writer’s attention was the test item construction and its appropriateness towards the indicators. The design of this research was descriptive qualitative. The location of the research was the library of STKIP PGRI Banjarmasin, Jl.Sultan Adam Komp. H. Iyus No.18 Rt.23 Banjarmasin. The data source was the document of PPL II report. The document was taken from the students’ PPL II report year 2015. The population of the research was the PPL II report of the seventh semester students of English Department of STKIP PGRI Banjarmasin who had taken PPL II and who conducted the PPL II at Senior High school. Since the number of PPL II report consisted of more than 120 RPP reports, then the writers took a sample. The sampling technique used was proportional random sampling. The sample taken was 12 RPP reports which consisted of six reports for middle test and six reports for final test. The result of this research is the test item constructed in PPL II reports mostly inappropriate toward indicators. The inappropriateness (75%)are mostly caused by no test items provided in RPP.